2016
DOI: 10.1177/0883073816680770
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Outcomes in the 2014 Acute Flaccid Paralysis Cluster in Canada

Abstract: We describe the presenting features and long-term outcome of an unusual cluster of pediatric acute flaccid paralysis cases that occurred in Canada during the 2014 enterovirus D68 outbreak. Children (n = 25; median age 7.8 years) presenting to Canadian centers between July 1 and October 31, 2014, and who met diagnostic criteria for acute flaccid paralysis were evaluated retrospectively. The predominant presenting features included prodromal respiratory illness (n = 22), cerebrospinal fluid lymphocytic pleocytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 15 publications
5
61
0
1
Order By: Relevance
“…Following its first identification in 1962, only 699 cases of EV-D68 were reported in scientific literature before 2014 [14]. From 2014 onwards, the epidemiology appears to have changed, and EV-D68 has increasingly been associated with outbreaks of respiratory infections and a concurrent upsurge of AFM [15,16] with poor long-term prognosis [17,18]. We identified 15 sequences, collected from five countries, which formed a distinct cluster within subclade B3 not previously described in Europe, illustrating the rapid evolution and spread of EV-D68.…”
Section: Discussionmentioning
confidence: 99%
“…Following its first identification in 1962, only 699 cases of EV-D68 were reported in scientific literature before 2014 [14]. From 2014 onwards, the epidemiology appears to have changed, and EV-D68 has increasingly been associated with outbreaks of respiratory infections and a concurrent upsurge of AFM [15,16] with poor long-term prognosis [17,18]. We identified 15 sequences, collected from five countries, which formed a distinct cluster within subclade B3 not previously described in Europe, illustrating the rapid evolution and spread of EV-D68.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of monoplegia/monoparesis (period 1: upper extremity in 2 patients, lower extremity in 1 patient; period 2: upper extremity in 5 patients) is more characteristic of focal CNS involvement, such as that seen with neurotropic infectious pathogens rather than a post-infectious immune-mediated process. Monoplegia has been reported in some AFM cases from most case series covering 2014 and later, most commonly an upper extremity, reflecting the common cervical cord involvement [17,18,[22][23][24][25][26]. The CSF WBC counts were low in many period 1 cases, which may suggest differences in pathogenesis between period 1 and period 2 cases.…”
Section: Discussionmentioning
confidence: 97%
“…However, among the subset of 74 cases from 2018 with CSF specimens tested at CDC, a pathogen was identified in only 2 cases (EV-D68 and EV-A71 in one CSF specimen each) [20,21]. Non-poliovirus AFM cases have also been reported from several other countries in the recent past [22][23][24][25][26]. The clinical and radiological phenotype termed AFM can be caused by pathogens other than polioviruses, including other enteroviruses (EV-A71) and certain flaviviruses (West Nile virus) [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…EV-D68 is the most consistent enterovirus linked with AFM (Kreuter et al, 2011), accounting for up to 50% of all confirmed AFM cases (Lopez et al, 2019), but other enteroviruses such as EV-A71 (Chumakov et al, 1979;Lopez et al, 2019;Lee et al, 2014), CVs (Cho et al, 2017;Lopez et al, 2019), EV-D70 (Bharucha et al, 1972), EV-B93 and EV-D94 (Junttila et al, 2007), echovirus 33 (Grimwood et al, 2003) and echovirus 11 (Moline et al, 2018;Lopez et al, 2019) have also been identified but at a much lower frequency. Although AFM is rare, affecting more than 500 confirmed cases worldwide since 2012 , the prognosis is poor with less than 20% of children fully regaining neurological function within 6 months (Sejvar et al, 2016;Yea et al, 2017;Helfferich et al, 2019). No treatment strategy currently exists for AFM patients but physical rehabilitation which, when implemented during the acute phase of the illness, slightly helps improve long-term neurological outcomes (Van Haren et al, 2015).…”
Section: Acute Flaccid Paralysis and Acute Flaccid Myelitismentioning
confidence: 99%